Chemical, Biological and Pharmacological Activities of Ficus religiosa: an Extensive Review - Sultana, Sifat Ara; Talukder, Shusmita; Shawon, Nusrat Jahan; Aktar, Fahima; Chowdhury, Jakir Ahmed; Chowdhury, Abu Asad; Kabir, Shaila; Amran, Md Shah (Bangladesh Pharmaceutical Journal, 2024)
Herbal drugs are one of the world’s oldest and most precious gifts. Medicinal herbs and plants have a prominent place in the healthcare system, with Ficus religiosa, being one of the most important. It is commonly knowns as fig, which is widely used in traditional medicinal systems as antiulcer, anticonvulsant, wound healing, antinephropathic, antiviral, analgesic, anti-inflammatory, antimicrobial, immunostimulant, antihyperlipidemic, antioxidant, antiasthmatic, parasympathetic modulatory, anti-acetylcholinesterase, anticancer and cognitive enhancing agents. Secondary metabolites isolated from the plant such as stigmasterol, methyl oleanolate, lanosterol, caffeic acid, bergenin, amides, lupin 3-one, β-sitosterol, n-octacosanol, and flavonoids are considered to be the principal bioactive compounds of F. religiosa. The purpose of this review was to outline the phytochemistry, pharmacology and toxicity profile of F. religiosa. Aside from plant morphology and phytochemistry, the application of the plant in the most recent discoveries and nanotechnology was also explored. Furthermore, the review addresses recent therapeutic breakthroughs and identifies areas for further research that should be addressed in future studies. Bangladesh Pharmaceutical Journal 27(2): 223-238, 2024 (July)